Carbon mitigation in the electric power sector under cap-and-trade and renewables policies. (May 2016) - Delarue, Erik; Van den Bergh, Kenneth
Abstract: In Europe, CO2 emissions from the electric power sector and energy intensive industries are capped under a cap-and-trade system (i.e., the EU ETS). When other indirect measures are taken to impact emissions in a specific sector under the cap (such as a push for renewables in the electric power sector), this has implications on the overall allowance price, and on CO2 emissions both from this specific sector and the other sectors under the cap. The central contribution of this paper is the derivation of impact curves, which describe these interactions, i.e., the impact on allowance price and the shift of emissions across sectors. From a set of detailed simulations of the electric power system operation, a so-called "emission plane" is obtained, from which impact curves can be derived. Focus is on interactions between CO2 abatement through fuel switching and measures affecting the residual electricity demand (such as deployment of renewables) in the electric power sector, as well as on interactions with other sectors, both in a short-term framework. A case study for Central-Western Europe is presented. The analysis reveals a substantial impact of renewables on CO2 emissions, and hence on emissions shifts across sectors and/or on the CO2 price. Highlights: CO2 cap-and-trade interacts with policies targeting one specific sector under cap. Interaction creates emission displacement and/or impacts CO2 price. The central contribution is the derivation of impact curves from the emission plane. The method is applied to a case study of Central-Western Europe. The analysis reveals a large impact of renewables on CO2 displacement and/or price.